2008
DOI: 10.2105/ajph.2007.115618
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between In-Home Water Service and the Risk of Respiratory Tract, Skin, and Gastrointestinal Tract Infections Among Rural Alaska Natives

Abstract: Higher respiratory and skin infection rates were associated with a lack of in-home water service. This disparity should be addressed through sanitation infrastructure improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(146 citation statements)
references
References 13 publications
3
142
0
1
Order By: Relevance
“…Among these are several transmissible diseases for which spread is associated with inadequate levels of sanitation and hygiene, housing shortages, and domestic water supply shortages . Similar waterehealth relationships have been investigated in Aboriginal communities in rural Alaska, which have some geographical and sociocultural similarities to Inuit communities in Canada's Arctic (Hennessy et al, 2008). Inuit populations are also at higher risk of exposure to environmental contaminants due to aspects of a traditional diet as compared to the average Canadian diet.…”
Section: Discussionmentioning
confidence: 76%
“…Among these are several transmissible diseases for which spread is associated with inadequate levels of sanitation and hygiene, housing shortages, and domestic water supply shortages . Similar waterehealth relationships have been investigated in Aboriginal communities in rural Alaska, which have some geographical and sociocultural similarities to Inuit communities in Canada's Arctic (Hennessy et al, 2008). Inuit populations are also at higher risk of exposure to environmental contaminants due to aspects of a traditional diet as compared to the average Canadian diet.…”
Section: Discussionmentioning
confidence: 76%
“…First, although several recent studies have demonstrated the relationships between in-home water service, sanitation, and health in rural Alaskan villages (Hennessy et al 2008;Chambers et al 2009;Wenger et al 2010), generally individual village population sizes are too small to undertake many epidemiological studies necessary to demonstrate the relationship between water service levels and the local health concerns of a specific village. In contrast, economic assessments of specific villages are conducted on a regular basis, providing data that ends up having more weight in the decisionmaking process.…”
Section: Journal Of Political Ecologymentioning
confidence: 99%
“…But approximately one third of households in remote Alaska lack running water and sewers, and the majority of these are in Alaska Native villages. Many villages lack in-home water and wastewater systems entirely, and experience high rates of lower respiratory and skin infections (Hennessy et al 2008;Wenger et al 2010), as well as periodic epidemics (U.S. Congress 1994), cross-contamination from sewage, and diseases transmitted orally or through fecal contamination (Chambers et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…According to Ford et al (2010: 670) in the Arctic: "Warmer weather [and] summers have the potential to increase the incidence of water and insect borne disease (e.g. Entamoeba histolytica, Giardia lamblia, Cryptosporidium parvum) (Hennessy et al, 2008;Martin et al, 2007), while rising temperatures are expected to increase the incidence of temperature-dependant, food-borne diseases, including Salmonella, as well as toxins produced by Staphylococcus aureus and Clostridium botulinm (Parkinson et al, 2008)." According to studies carried out by various scholars (Archibald et al, 1991;Turner and Turner, 2008;Turner and Clifton, 2009;Kuhnlein et al, 2009), communities in the subarctic and boreal latitudes have reported anthropogenic, ecological and climate change impacts associated with access to safe drinking water and traditional foods, reduced physical activity, changing ice conditions, and unpredictable weather patterns, all of which impact health (physical, mental, and spiritual) and well-being.…”
Section: Study Areamentioning
confidence: 99%